Infant Sleep Location and Breastfeeding Practices in the United States, 2011–2014 - Smith, Lauren A.; Geller, Nicole L.; Kellams, Ann L.; Colson, Eve R.; Rybin, Denis V.; Heeren, Timothy; Corwin, Michael J. (Academic pediatrics, 2016)
To describe the prevalence of breastfeeding and sleep location practices among US mothers and the factors associated with these behaviors, including advice received regarding these practices. A nationally representative sample of 3218 mothers who spoke English or Spanish were enrolled at a sample of 32 US birth hospitals between January 2011 and March 2014. Exclusive breastfeeding was reported by 30.5% of mothers, while an additional 29.5% reported partial breastfeeding. The majority of mothers, 65.5%, reported usually room sharing without bed sharing, while 20.7% reported bed sharing. Compared to mothers who room shared without bed sharing, mothers who bed shared were more likely to report exclusive breastfeeding (adjusted odds ratio 2.46, 95% confidence interval 1.76, 3.45) or partial breastfeeding (adjusted odds ratio 1.75, 95% confidence interval 1.33, 2.31). The majority of mothers reported usually room sharing without bed sharing regardless of feeding practices, including 58.2% of exclusively breastfeeding mothers and 70.0% of nonbreastfeeding mothers. Receiving advice regarding sleep location or breastfeeding increased adherence to recommendations in a dose response manner (the adjusted odds of room sharing without bed sharing and exclusive breastfeeding increased as the relevant advice score increased); however, receiving advice regarding sleep location did not affect feeding practices. Many mothers have not adopted the recommended infant sleep location or feeding practices. Receiving advice from multiple sources appears to promote adherence in a dose response manner. Many women are able to both breastfeed and room share without bed sharing, and advice to adhere to both of these recommendations did not decrease breastfeeding rates.